Risk Factors for Development of Moderate and Severe Dehydration in Young Children with Acute Watery Diarrhea - Raed Abdulameer Mirdan; Najlaa Jaafar Ali (Academic Journal of Clinicians, 2025)
Background: Diarrhoea is a primary cause of sickness and mortality among children in underdeveloped nations. Acute-onset diarrhoea is often self-limiting; nevertheless, an acute infection may have a prolonged duration. The predominant complication of severe diarrhoea is dehydration. Diarrhoeal diseases can substantially affect psychomotor and cognitive development in young children. Objective: To detect the risk factors for development of moderate and severe dehydration in children below two years with acute watery diarrhea. Patients and methods: A hospital based case-control study, in which children aged up to 2 years of age suffering from acute watery diarrhea admitted to Al-Imamin Al-Kadhmin Teaching hospital, between February 2023 to December 2023 in which 222 child were included in the study to determine the risk factors for development of moderate to severe dehydration in patients with acute watery diarrhea, children comprising 102 cases (moderate or severe dehydration) and 120 controls (no or mild dehydration) up to 2 years of age suffering from acute watery diarrhea were studied. Results: The statically significant risk factors for the onset of mild to severe dehydration in acute watery diarrhea that were identified include : Infancy below one year of age ( 84 children, 82% of cases , p value =0.0001, OR =2.08 ) , artificial feeding ( 74 children , 72.5% , p value =0.0005) , withdrawal of breast feeding during diarrhea (63 children, 61.7% of cases , OR =2.11 , p value= 0.0004) , poverty (41children ,40% of cases , OR =4.7, p value=0.0001 ), residency in rural area (65 children , 63.7% of cases , OR = 2.07, p value= 0.008), cessation or reduction of home fluid (55children , 54% of cases , OR = 2.17, p value=0.005) and ORS (76 children, 74.5% of dehydrated cases, OR = 2.47 , p value=0.002) during diarrheal episode, frequency of stools >8/day (75children, 73.5%, OR = 3.75, p value=0.003), frequency of vomiting>2/ day (77 children , 75.4% , OR = 3.7, p value=0.001) and temperature>38c (76 children , 74.5%, OR= 2.55, p value 0.001) and malnutrition (p value =0.0002). Conclusions: This study suggest that early infancy, severe or moderate malnutrition, poverty, bottle feeding whether mixed or alone, early development of high grade temperature , more frequent vomiting or stool per day and rural residency are risk factors for dehydration in young children with acute watery.